New material and design concepts for constructions of vehicles – challenges for thermal an cold joining techniques - Meschut, Gerson; Goede, M. (Tagungsband zur 9. International Aachen Welding Conference: Joining in Traffic and Transportation Industry – Processes, Progress, Applications)

Kleben und Hybridfügen von Leichtbaustrukturen für den Automobilbau - Disse, T.; Maciej, M.; Meschut, Gerson; Piccolo, S.; Timmermann, R.; Wibbeke, T.-M. (Adhäsion)

Mechanische Fügetechnik für die Mischbauweise – Teil 1: Systemoptimierungen - Letsch, S.; Meschut, Gerson; Küting, J.; Peitz, V.; Timmermann, R.; Schmid, L. (Schweißen und Schneiden)

Material-Secific joining techniques for magnesium body structures - Hahn, O.; Schumann, S.; Meschut, Gerson; Fuhrmann, T.

Mechanische Fügetechnik für die Mischbauweise – Teil 2: Neuartige Fügeverfahren - Letsch, S.; Meschut, Gerson; Küting, J.; Peitz, V.; Timmermann, R.; Schmid, L. (Schweißen und Schneiden)

Simple On-Line Algorithms for the Maximum Disjoint Paths Problem - Kolman, Petr; Scheideler, Christian (Algorithmica)

Group Spreading: A Protocol for Provably Secure Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (ICALP)

A Distributed Hash Table for Computational Grids - Riley, Chris; Scheideler, Christian (IPDPS)

Zukünftige Werkstoff- und Bauweisenkonzepte im Automobilbau - Herausforderungen für die Gewindetechnologie - Meschut, Gerson (Tagungsband zum 2. Böllhoff-Fachkolloquium)

Fügen von Kunststoffen im strukturellen Leichtbau - Bye, C.; Draht, T.; Küting, J.; Lübbers, R.; Meschut, Gerson; Ruther, M. (Tagungsband zum 11. Paderborner Symposium Fügetechnik „Mechanisches Fügen und Kleben“)

Robust Distributed Name Service - Awerbuch, Baruch; Scheideler, Christian (IPTPS)

Druckfügeverfahren und damit hergestellte Rahmen - Hahn, O.; Meschut, Gerson

Fügeverfahren und Fügevorrichtung zum Verbinden von überlappend angeordneten Fügeteilen - Amedick, Jürgen; Hahn, Ortwin; Kurzok, Jan; Letsch, Stefan; Meschut, Gerson; Peitz, Volker; Timmermann, Rüdiger

Survivable Monitoring in Dynamic Networks - Ateniese, Giuseppe; Riley, Chris; Scheideler, Christian (IWIA)

The hyperring: a low-congestion deterministic data structure for distributed environments - Awerbuch, Baruch; Scheideler, Christian (SODA)

Consistent and compact data management in distributed storage systems - Awerbuch, Baruch; Scheideler, Christian (SPAA)

Pagoda: a dynamic overlay network for routing, data management, and multicasting - Bhargava, Ankur; Kothapalli, Kishore; Riley, Chris; Scheideler, Christian; Thober, Mark (SPAA)

The effect of faults on network expansion - Bagchi, Amitabha; Bhargava, Ankur; Chaudhary, Amitabh; Eppstein, David; Scheideler, Christian (SPAA)

math-kit - Ein multimedialer Baukasten für die Mathematikausbildung im Grundstudium - Unger, L.; Bauch, M.; Baudry, A.; Bungenstock, M.; Mertsching, B.; Oevel, Gudrun; Padberg, K.; Thiere, B. (SoftwareTechnikTrends)

V:Drive - Costs and Benefits of an Out-of-Band Storage Virtualization System - Brinkmann, André; Heidebuer, Michael; Meyer auf der Heide, Friedhelm; Rückert, Ulrich; Salzwedel, Kay; Vodisek, Mario (21st IEEE Conference on Mass Storage Systems and Technologies / 12th NASA Goddard Conference on Mass Storage Systems and Technologies, Greenbelt, Maryland, USA)

Optical properties of planar metallic photonic crystal structures: Experiment and theory - Christ, A.; Zentgraf, Thomas; Kuhl, J.; Tikhodeev, S. G.; Gippius, N. A.; Giessen, H. (Physical Review B)

Tailoring the Ultrafast Dephasing of Quasiparticles in Metallic Photonic Crystals - Zentgraf, Thomas; Christ, A.; Kuhl, J.; Giessen, H. (Physical Review Letters)

Wolff, Christian Freiherr von - Peckhaus, Volker (Lexikon der bedeutenden Naturwissenschaftler in drei Bänden, Bd. 3: Men–Z)

Smoothed Number of Extreme Points under Uniform Noise - Sohler, Christian; Damerow, Valentina (Proceedings of the 20th European Workshop on Computational Geometry (EWCG'04))

Extreme Points Under Random Noise - Damerow, Valentina; Sohler, Christian (Proceedings of the 12th European Symposium on Algorithms (ESA'04))
Given a point set P in the d-dimensional unit hypercube, we give upper bounds on the maximal expected number of extreme points when each point is perturbed by small random noise chosen independently for each point from the same noise distribution Δ. Our results are parametrized by the variance of the noise distribution. For large variance we essentially consider the average case for distribution Δ while for variance 0 we consider the worst case. Hence our results give upper bounds on the number of extreme points where our input distributions range from average case to worst case. Our main contribution is a rather general lemma that can be used to obtain upper bounds on the expected number of extreme points for a large class of noise distributions. We then apply this lemma to obtain explicit bounds for random noise coming from the Gaussian normal distribution of variance σ² and the uniform distribution in a hypercube of side length &epsilon. For these noise distributions we show upper bounds of O( (1/ σ )^d * log^3/2 * d - 1 n ) and O( ( (n log n) / ε )^d/(d+1) ), respectively. Besides its theoretical motivation our model is also motivated by the observation that in many applications of convex hull algorithms the input data is inherently noisy, e.g. when the data comes from physical measurement or imprecise arithmetic is used.

Reducing State Changes with a Pipeline Buffer - Sohler, Christian; Krokowski, Jens; Räcke, Harald; Westermann, Matthias (Proceedings of the Vision, Modeling, and Visualization Conference (VMV 2004))
A limiting factor in the performance of a render- ing system is the number of state changes, i.e., changes of the attributes material, texture, shader program, etc., in the stream of rendered primitives. We propose to include a small buffer between appli- cation and graphics hardware in the rendering sys- tem. This pipeline buffer is used to rearrange the incoming sequence of primitives on-line and locally in such a way that the number of state changes is minimized. This method is generic; it can be easily integrated into existing rendering systems. In our experiments a pipeline buffer reduces the number of state changes by an order of magnitude and achieves almost the same rendering time as an optimal, i.e., presorted, sequence without pipeline buffer. Due to its simple structure and its low mem- ory requirements this method can easily be imple- mented in software or even hardware.

Sublinear-Time Approximation for Clustering via Random Sampling - Sohler, Christian; Czumaj, Artur (Automata, Languages and Programming (ICALP))

Literaturwissenschaft - Eke, Norbert Otto; Allkemper, Alo
2. Auflage 2006

Channel Adaptive Techniques in the Presence of Channel Prediction Inaccuracy - Aguiar, Ana; Karl, Holger; Wolisz, Adam (Proceedings of European Wireless 2004, Barcelona / Spain)

Einleitung „in der zeit“ – kunst aus sachsen-anhalt 2004 - Seng, Eva- Maria (Katalog der Landeskunstausstellung Sachsen-Anhalts in Magdeburg 2004)

Götter in der Stadt oder: „Wo Aas ist, sammeln sich die Geier!“ Stadtuntergänge bei Brecht und Trolle - Eke, Norbert Otto (Mahagonny.com. The Brecht Yearbook 29)

Intermedialität und Theatralisierung: Peter Greenaways Film-Theater - Eke, Norbert Otto (Crossing Media. Theater – Film – Fotografie – Neue Medien)

Eingebunkert – Stalin/Hitler: eine Konfiguration - Eke, Norbert Otto („Der Text ist der Coyote“. Heiner Müller Bestandsaufnahme)

Stressmodelle und Analyse der Hirntätigkeit - Weiß, M; Barthel, T; Baumeister, Jochen (ForschungsForum)

Teaching Object-Oriented Concepts with Eclipse - Meyer, Matthias; Wendehals, Lothar (Proc. of the Eclipse Technology eXchange Workshop (ETX), Satellite Event of the 19th Conference on Object-Oriented Programming, Systems, Languages, and Applications (OOPSLA), Vancouver, Canada)
Object-oriented software development is a subject area difficult to teach, espcially to beginners. They face a lot of abstraction and (from a beginners point of view) isolated topics, such as the syntax and semantics of a programming language, the functionality of a software development environment and basic object-oriented concepts. Although many professionals in education believe in the ``object first'' approach as the best method of introducing object-oriented concepts, there is no common agreement on how to start such courses. Current study programs often begin by teaching a programming language, instead of focusing on the basics of object-oriented concepts. In the last years a learning environment was developed based on a visual programming language to abstract away from details. It assists teaching step-by-step object-oriented concepts and the syntax and semantics of a programming language in secondary schools and first year university courses. Our goal is to port this learning environment to the widely used IDE Eclipse.

Selective Tracing of Java Programs - Wendehals, Lothar; Meyer, Matthias; Elsner, Andreas (Proc. of the 2nd International Fujaba Days 2004, Darmstadt, Germany)
Design recovery, which means extracting design documents from source code, is usually done by static analysis techniques. Analysing behaviour by static analysis is very imprecise. We combine static and dynamic analysis to increase the preciseness of our design recovery process. In this paper we present an approach to collect data for the dynamic analysis by recording method calls during a program's execution. To reduce the amount of information we monitor only relevant classes and methods identified by static analysis.

Aktuelle Änderungen beim Betriebsausgabenabzug - Geschenke, Bewirtungskosten, Fahrtkostenzuschüsse und Halbjahres-AfA - Sureth-Sloane, Caren; Müller, Jens; Nordhoff, Daniel (BBK - Buchführung, Bilanzierung, Kostenrechnung)

Computability in linear algebra - Ziegler, Martin; Brattka, Vasco (Theoretical Computer Science)

Computable operators on regular sets - Ziegler, Martin (Computability and Complexity in Analysis)
For uniform computability of regular sets in Euclidean space, previous work has identified twelve 'basic' notions, to (pairs of) which many previous notions considered in literature were shown to be equivalent. With respect to those basic notions, we now investigate on the computability of natural OPERATIONS on regular sets: union, intersection, complement, convex hull, image, and pre-image under suitable classes of functions.

Fast Multipoint Evaluation of Bivariate Polynomials - Nüsken, Michael; Ziegler, Martin (Proc. 12th Annual Symposium on Algorithms (ESA'04))
We generalize univariate multipoint evaluation of polynomials of degree n at sublinear amortized cost per point. More precisely, it is shown how to evaluate a bivariate polynomial p of maximum degree less than n, specified by its n^2 coefficients, simultaneously at n^2 given points using a total of O(n^2.667) arithmetic operations. In terms of the input size N being quadratic in n, this amounts to an amortized cost of O(N^0.334) per point.

Spanners, Weak Spanners, and Power Spanners for Wireless Networks - Schindelhauer, Christian; Volbert, Klaus; Ziegler, Martin (Proc. of 15th Annual International Symposium on Algorithms and Computation (ISAAC'04))
For $c in REAL$, a $c$-spanner is a subgraph of a complete Euclidean graph satisfying that between any two vertices there exists a path of weighted length at most $c$ times their geometric distance. Based on this property to approximate a complete weighted graph, sparse spanners have found many applications, e.g., in FPTAS, geometric searching, and radio networks. For geometric searching, it turned out to suffice whether the radius rather than the length of some path between any two vertices is bounded relatively to their geometric distance; this is the defining property of weak spanners. Finally regarding radio network applications, a power spanner accounts for the total energy afforded for a wireless transmission with the requirement that the sum of the squares of the lengths of some path between any two planar vertices must be bounded relatively to the square of their geometric distance (or higher powers up to 6 or even 8). While it is known that any $c$-spanner is also both a weak $C_1$-spanner and a $C_2$-power spanner (for appropriate $C_1,C_2$ depending only on $c$ but not on the graph under consideration), we show that the converse fails: There exists a family of $c_1$-power spanners that are no weak $C$-spanners and also a family of weak $c_2$-spanners that are no $C$-spanners for any fixed $C$ (and thus no uniform spanners, either). However the deepest result of the present work reveals that, surprisingly, any weak spanner is also a uniform power spanner. We further generalize the latter notion by considering $(c,delta)$-power spanners where the sum of the $delta$-th powers of the lengths has to be bounded; so $(cdot,2)$-power spanners coincide with the usual power spanners and $(cdot,1)$-power spanners are classical spanners. Interestingly, these $(cdot,delta)$-power spanners form a strict hierarchy where the above results still hold for any $deltageq2$; some even hold for $delta>1$ while counterexamples reveal others to fail for $delta<2$. In fact we show that in general every self-similar curve of fractal dimension $d>delta$ is no $(C,delta)$-power spanner for any fixed $C$.

Guidance of Users in Interactive 3D-Visualisations of Material Flow Simulations - Mueck, Bengt; Dangelmaier, Wilhelm; Laroque, Christoph; Fischer, Matthias; Kortenjan, Michael (Simulation and Visualisation 2004)
The visualisation of manufacturing-processes assists the user in understanding and analysis. Typically he can move free and unguided in a virtual environment which visualizes the entire process. Thus knowledge and conclusions are to some extend acquired on a random base. This article describes the development of a tool, which enables the user to interactively improve significant production processes in the simulation. He moves in a virtual 3D-environment (walkthrough system) and is able to acquire automatically calculated indications for significant processes. At the same time the simulation considers significant objects in a more detailed way. If the viewer is interested in a significant process, he is automatically guided to the relevant location where he can examine the critical situation by modification of the simulation model.

Transcoding von Webinhalten - Oesterdiekhoff, Brigitte (Informatik Spektrum)

Internet Premium Services for Flexible Format Distributed Devices - Oesterdiekhoff, Brigitte (Proceedings of IFIP Working Conference on Distributed and Parallel Embedded Systems (DIPES'04))

Bereichsübergreifendes Toleranzmanagement. Damit es rund läuft - Kretschmer, Ralf; Denzer, Vera; Zimmer, Detmar (QZ - Qualität und Zuverlässigkeit)

Faserverbundwerkstoffe - experimentelle Bestimmung mechanischer Kenngrößen - Koke, Isabel; Funke, Herbert; Ferber, Ferdinand (Posterbeitrag AG Composite)

Integrated Vehicle Dynamics Control Using Active Brake, Steering, and Suspension Systems - Trächtler, Ansgar (Int. J. Vehicle Design)

Verteilte Fahrdynamikregelung mit zeitgesteuerter Architektur am Beispiel des Bosch-Konzeptes VDM - Albert, Amos; Trächtler, Ansgar (13. Aachener Kolloquium Fahrzeug- und Motorentechnik)

Zusammenspiel von regelbaren Feder-/Dämpfersystemen mit ESP - Trächtler, Ansgar (CTI-Konferenz "Federung und Dämpfung")

Integrierte Fahrdynamikregelung mit ESP, aktiver Lenkung und aktivem Fahrwerk - Trächtler, Ansgar (2. VDI/VDE-Fachtagung zur Steuerung und Regelung von Fahrzeugen und Motoren AUTOREG)